Pengaruh Motivasi Belajar, Minat Belajar, dan Manajemen Waktu terhadap Prestasi Belajar Siswa pada Masa Pembelajaran Tatap Muka Terbatas - Yulyani, Rani Dewi (Edumaspul: Jurnal Pendidikan, 2022)
The Research aims to examine the effect of learning motivation, interest, and time management to the learning achievement on limited face to face learning for students of Arabic language and literature Ushuluddin and Adab Faculty Islamic State University (UIN) Sultan Maulana Hasanuddin Banten. The sample of research are 118 students. Data analysis technique on the research is descriptive analysis and regression analysis with the help of SPSS 21 program. The result of the research showed that learning motivation significantly effect to learning achievement, learning interest significantly effect to learning achievement, and time management significantly effect to learning achievement. Learning motivation affects 15,97%, learning interest affects 17,86% and time management affects 19,96%. The result of learning motivation, learning interest, and time management in total have 53,79% to learning achievement